Antagonistic efficacy of Trichoderma harzianum and Bacillus cereus against Ganoderma disease of oil palm via dip, place and drench (DPD) artificial inoculation technique - Syd Ali, Nusaibah; Saad, Ghazala; Tan, Geok Hun (Friends Science Publishers, 2017)
Sustainability of the oil palm industry is crucial to ensure Malaysia's gross domestic product (GDP) by the agricultural sector. It is crucial to discover a sustainable and eco-friendly remedy for the most devastating Ganoderma disease of oil palm. The effects of pre-inoculation of oil palm seedlings with either Trichoderma harzianum and/or Bacillus cereus on their vegetative growth and the suppression of Ganoderma boninense were investigated. The dip, place and drench (DPD) artificial inoculation method was used to assure disease development. Disease severity was assessed based on the root symptoms (DS), disease incidence (DI) and disease reduction (DR). Application of a mixture of T. harzianum and B. cereus had the highest contribution to the vegetative growth of oil palm seedlings. However, single application of B. cereus was found to be the most effective treatment in suppressing Ganoderma disease of oil palm with a disease reduction of 94.75% followed by single applications of T. harzianum (78.98%) and mixture of both T. harzianum and B. cereus (68.49%).